Age stereotypes and subjective age: Influences and indicators of successful aging? - Petery, Gigi; Laguerre, Rick; Burch, Katrina; Barnes-Farrell, Janet (2019)
Successful aging has been defined in terms of flourishing late in life as determined by subjective and objective health, happiness, and satisfaction criteria (Depp & Jeste, 2006; Zacher, 2015a). Further, there are three dynamic trajectories to aging, namely growth, change, and decline (Vaillant & Mukamal, 2001). Successful aging at work, which is encapsulated in the global concept, captures these developmental trajectories in terms of subjective and objective individual (e.g., attitudes, well-being, work ability, health, and motivation) and work (e.g., performance ratings, turnover, and retirement intentions) outcomes (Kooij, 2015; Zacher, 2015a, 2015b). Zacher’s (2015b) theoretical framework of successful aging at work proposed a number personal and contextual mediators and moderators that likely influence outcomes of interest. For example, he suggested that age related social contextual factors, such as stereotypes, may change as a worker ages. However, there is evidence that age stereotypes have changed little over time (Petery & Barnes-Farrell, 2016). Moreover, according to stereotype embodiment theory (Levy, 2009), age stereotypes are ubiquitous and can shape how individuals expect to experience their own aging process, namely through internalizing age stereotypes which, over time, can shape self-perceptions of aging. In essence, age stereotypes operate subconsciously and may dictate what to expect with, and how to behave in, older age; that, in turn, may lead to embodying those stereotypes when one passes into old age. Although both positive and negative general and work specific age stereotypes exist, negative stereotypes have a greater influence on attitudes concerning, perceptions about, and behaviors towards older adults (Hummert, Garstka, Ryan, & Bonnesen, 2004). There is a growing body of research demonstrating the effect of attitudes toward aging on individual health and well-being. For example, a pair of longitudinal studies by Levy and colleagues showed that positive self-perceptions of aging resulted in better functional health and increased longevity 18 to 23 years later (Levy, Slade, & Kasl, 2002; Levy, Slade, Kunkel, & Kasl, 2002). Experimental research by Kotter-Grühn and Hess (2012) revealed that priming with negative age stereotypes resulted in adults of all ages being less satisfied with their chronological age. They reasoned this might reflect anxiety towards anticipated negative age-related changes. Furthermore, implicit age stereotypes can trigger self-stereotyping effects. Levy (1996) primed older adults with negative or positive stereotypes. Those primed with negative stereotypes experienced posttest declines in memory performance, while those primed with positive stereotypes improved performance. In a follow-up study, implicit positive age stereotypes improved handwriting ability, while implicit negative age stereotypes resulted in shakier handwriting (Levy, 2000). In an effort to further understand the role age stereotypes play in the aging process, we used a qualitative approach to ask working adults directly about their beliefs about age and aging. The overarching aim of the study was to examine how age stereotypes shape aging perceptions and expectations. Recognizing that survey responses may mask implicit attitudes about aging (Greenwald, & Banaji, 1995; Hummert et al., 2004), we conducted 30 semi-structured interviews with working adults (age: range: 22-70, M = 39.1, SD = 16.4; 50% male; 86.7% white; 93.3% college or graduate degrees; 56.7% married or living with partner) on their beliefs about their age and aging, both in general and in their work environment. A non-random, purposeful sampling strategy was used to select participants for this study. Through a pre-screen survey, we identified 99 individuals who indicated they worked 30 or more hours per week for pay and thought about their age often or always. To ensure a wide age distribution and equal number of male and female participants, we divided the pool of eligible individuals into three age categories: “young”-aged (18-25 years old), “middle”-aged (26-45 years old), and “old”-aged (46 and older). Invitations were sent, in order of receipt of pre-screen survey, until 10 individuals (half male) in each age category were successfully recruited and interviewed. A constructivist/interpretive perspective was taken to address our research questions. This perspective “assumes that reality is socially constructed” and “that there are multiple realities, or interpretations, of a single event” (Merriam & Tisdell, 2016, p. 9). We conducted what Merriam and Tisdell (2016) refer to as a basic qualitative study to understand how personal experiences shape perceptions and attitudes, and employed thematic analysis (Braun & Clarke, 2006) to identify themes and patterns in the data. Young-aged participants’ themes corresponded to stereotypes associated with life stages, such as loss of childhood freedom and anticipating career growth and starting a family. Themes among the middle- and old-aged participants revealed that age stereotype guided expectations about growing older. Specifically, positive expectations toward aging reflected positive stereotypes, which were often associated with general, as well as work specific, growth (e.g., wisdom/experience, self-confidence, financial security). Negative expectations toward aging expressed stereotypes typically associated with declines (e.g., declines in mental and physical functioning, loss of independence). This indicates that different time horizons are used when evaluating positive and negative aspects of aging, and these vary depending on age-related factors (e.g., life experiences). Surprisingly, health declines (e.g., taking longer to recover from physical exertion) were attributed to being old, even for the youngest participants in the “middle”-aged group (i.e., late-twenties). Through this qualitative study we identified themes that are consistent with age-related stereotypes. Our findings shed light on how stereotypes influence perceptions of age and aging from early adulthood on. For our participants, it appeared that age stereotypes colored their expectations for aging. This is important because these expectations likely inform attitudes about aging, which, in turn, may act to impede or facilitate successful aging. Because ignoring or eliminating negative age stereotypes might be difficult, future research should explore the impact that positive examples and role models of successful aging have on aging expectations. An additional suggestion for future research is to examine how policies aimed at facilitating and capitalizing on age related gains, while downplaying age-related declines, might foster a more positive outlook on aging.